2014
DOI: 10.1371/journal.pntd.0002764
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of Differentially Expressed Proteins from Leishmania amazonensis Associated with the Loss of Virulence of the Parasites

Abstract: BackgroundThe present study analyzed whether or not the in vitro cultivation for long periods of time of pre-isolated Leishmania amazonensis from lesions of chronically infected BALB/c mice was able to interfere in the parasites' infectivity using in vivo and in vitro experiments. In addition, the proteins that presented a significant decrease or increase in their protein expression content were identified applying a proteomic approach.Methodology/Principal FindingsParasites were cultured in vitro for 150 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 93 publications
(162 reference statements)
8
46
1
2
Order By: Relevance
“…Loss of virulence can also be achieved by axenic culture for many passages . L. amazonensis promastigotes cultured for 10, 20, and 30 passages displayed decrease in macrophage infection and changes in proteome as detected by 2DE . Extended culture led to a decrease in proteins such as TXNPx, malic enzyme, enolase, and carboxypeptidase, enzymes known to be involved in virulence of Leishmania or other pathogens …”
Section: Potential Applications Of Proteomics In Leishmaniasismentioning
confidence: 97%
“…Loss of virulence can also be achieved by axenic culture for many passages . L. amazonensis promastigotes cultured for 10, 20, and 30 passages displayed decrease in macrophage infection and changes in proteome as detected by 2DE . Extended culture led to a decrease in proteins such as TXNPx, malic enzyme, enolase, and carboxypeptidase, enzymes known to be involved in virulence of Leishmania or other pathogens …”
Section: Potential Applications Of Proteomics In Leishmaniasismentioning
confidence: 97%
“…infantum ELISA; LC–MS/MS Post infection vs pre infection 19 12 2019 [ 48 ] 12 L . infantum ELISA; RP‐ LC‐MS/MS After infection 168 days vs before infection, 211 days after infection vs before infection and 211 days after infection vs 168 days after infection 15 15 2020 [ 47 ] 13 Proteins of Leishmania Between infective strain L. infantum 2DE; MALDI-TOF/TOF MS Abundance volume ratio in BH 400 strain of L. infantum vs BH 46 strain 32 31 2014 [ 50 ] 14 L. amazonensis IEF; 2DE; ESI-TOF MS/MS; Western blot Day 0 vs day 150 19 37 2014 [ 51 ] 15 L. donovani SDS-PAGE; Nano HPLC–MS/MS; Western blot VL vs CL 29 109 2015 [ 53 ] 16 L. tropica 2DE-MALDI-TOF/TOF MS Percent volume of spot in gel of VL vs CL 10 35 2015 [ 54 ] 17 <...>…”
Section: Differentially Modulated Proteins In the Host After mentioning
confidence: 99%
“…Despite the presence of a similar abundance level of other virulence-related proteins in both BH400 and BH46, the study reported higher signal intensity in the proteins of BH400. On the other hand, Magalhães et al [ 51 ] compared the protein modulations between severe (day 0 of culture) and less virulent (day 150 of culture) L. amazonensis and reported 56 differentially regulated proteins. Out of them, 19 and 37 proteins were up-regulated and down-regulated, respectively.…”
Section: Differentially Modulated Proteins Between Different Strains mentioning
confidence: 99%
“…Once internalized by phagocytic cells, they differentiate into non-motile amastigotes. The main life cycle stages of several Old World and New World species causing cutaneous leishmaniasis (CL), mucocutaneous leishmaniasis (MCL), or VL have been compared using high-throughput gene expression analysis (e.g., Akopyants et al 2004;Alcolea et al 2010;Holzer et al 2006;Magalhaes et al 2014;Saxena et al 2007). Most comparisons are focused on promastigote-intoamastigote development.…”
Section: Introductionmentioning
confidence: 99%